1996
DOI: 10.1007/bf00434545
|View full text |Cite
|
Sign up to set email alerts
|

Mar shortening osteotomy in posttraumatic ulnar impaction syndrome

Abstract: Twenty-eight patients (average age 45 years) with posttraumatic ulnar impaction syndrome underwent ulnar shortening osteotomy of 3-15 mm. Contributing factors were malunited fractures of the distal radius in 20, diaphyseal fractures of the ulna and radius in 6, resection of the radial head and a traumatic tear of the triangular fibrocartilage in 1 patient each. Evaluation at an average follow-up of 20 months showed a high rate of satisfied patients (89%), but according to Chun's modification of the Gartland-We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 13 publications
3
36
0
Order By: Relevance
“…Fricker et al followed 28 patients with post-traumatic ulnar impaction for an average of 20 months and found that 79% returned to their preoperative level of occupation [6]. Constantine et al found that 82% (9 of 11) patients returned to previous level of employment [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fricker et al followed 28 patients with post-traumatic ulnar impaction for an average of 20 months and found that 79% returned to their preoperative level of occupation [6]. Constantine et al found that 82% (9 of 11) patients returned to previous level of employment [5].…”
Section: Discussionmentioning
confidence: 99%
“…Early outcomes following ulna shortening osteotomy for the treatment of ulnar impaction syndrome have demonstrated good pain relief, satisfactory objective outcomes (motion, strength, and healing), and patient satisfaction [1,4,6,12,16]. The most commonly reported complications of ulnar shortening osteotomy are plate irritation (8-56%) and ulnar nonunion (approximately 5%) [2,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…35 Other advantages of ulnar shortening osteotomy are the maintenance of the cartilage surface at the distal ulna and the simplicity of the procedure without bone grafting. 20,[36][37][38] The disadvantages of ulnar shortening are nonunion/delayed union and hardware irritation. 6,10,15,[17][18][19] However, rates of complication can be low if the procedure is properly performed, 5,38 and many papers have actually reported low complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…20,30,[37][38][39] Combining the results using standard technique and equipment, 79 of 90 patients (88%) achieved good or excellent results regarding pain relief and recovery of function, with only one nonunion (1%). 5,9,14,18 Poor outcomes were associated with degenerative changes at the DRUJ, long duration of symptoms, smoking, and workers' compensation claims.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggests, although the wafer resection is easier to perform than ulnar shortening, removing the articular cartilage surface of the distal ulna may have consequences [16]. Fricker et al [8] reported 89% of patients were satisfied at 20 months when questioned. In this instance, a high rate of patient satisfaction was combined with rather poor Gartland-Werley wrist scores.…”
Section: Discussionmentioning
confidence: 99%